Pengaruh Dimensi Service Quality Terhadap Kepuasan Tamu Hotel dan Dampaknya Terhadap Behaviour Intention (Studi Kasus Pada Hotel Aston Kuningan Suites-Jakarta) - Zita Hanna Mariska; Muchsin Saggaff Shihab (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
This study aims to analyze the effect of service quality dimensions on customer satisfaction and its impact on customer satisfaction. Customers of Aston Hotel Kuningan Suites, Jakarta were taken as respondents.Â  Both primary and secondary data were gathered. Secondary data were gathered from various sources such as journals, books and other related publications. Primary data were collected using questionnaire which were distributed to the target respondents. Using a purposive sampling technique, a total of 100 respondents were gathered of which 75 responses were valid. Various statistical tests such as validity, reliability and classical assumptions tests were employed. The result showed that except empathy all service quality dimensions had a positive and significant effect on customer satisfaction. Also customer satisfaction had a positive and significant effect on behavior intention. Meanwhile, service quality dimensions except assurance had a positive and significant effect on behavior intention. It is suggested that the company should pay more attention on various aspects such as emotional and technical aspects. Further research on perceived prices and relationship is need.